Diseño de un modelo organizacional administrativo y de gestión, en función de la estructura orgánica y los procesos de la Universidad Nacional de Loja - Gutiérrez Sánchez, Ilia Auristela (2016)
The "DESIGN OF AN ADMINISTRATIVE AND ORGANIZATIONAL MODEL MANAGEMENT, BASED ON THE ORGANIZATIONAL STRUCTURE AND PROCESS OF NATIONAL UNIVERSITY LOJA" is the subject of research, where it may reveal new aspects of organization, facing the traditional vertical structure of institutions. It is proved that in any organization there must be an organizational structure to provide guidance in the development of the functions of each position, for which it is modeled by processes organizational structure, the same that has been adapted to all public institutions the country and which is not clear the level of responsibility of each of the members of the educational institution, in each of the processes: Rulers, Advisory Enabling, Enabling Support, and Value aggregators. At the National University of Loja, there has been no redesign, adjustment or vertically organizational innovation model, the same as it had been using since 1990 and which are not defined responsibilities, powers and functions products and results activities of faculty and staff. The purpose of this research is to provide the National University of Loja an Organizational Model for Process updated, allowing the fulfillment of the objectives set in the mission and vision of the institution of higher education, to ensure effectiveness and efficiency of the same. The methodology used in this research work, allowed to collect information related to the legal framework and the organization of public institutions, specifically public institutions of higher education, which is framed in the National University of Loja, in order to evaluate the profile of compliance, allowing to define a legitimate proposal, which is attached to reality and structure of the institution. The result is the proposal of the regulations contained in the Constitution of Organizational Management by Processes of the National University of Loja, the same which contains among others the structural organization of the National University of Loja, 37 items in which they determine the mission scope and products that are generated in each of the processes. For the proposed organizational structure of the National University of Loja, we performed a comparative analysis of the structure of the year 1999, with the functional organizational structure of other public universities nationwide, and the information held by the Chief of Staff National University of Loja, on the main functions that develop institutional administrative unit, obtaining as a result a Manual of Classification, Valuation and Job Description, for which we used the matrix managed by the Ministry of Labor Relations. This product, applied to the reclassification of university servers, enable the National University of Loja have a formal structure, legitimate and legal. Another product obtained in this investigation, is related to the remuneration, for which we propose the remuneration manage the staff working at the National University of Loja Distributive function of the Remuneration, to the effect, has been based on information provided by the Ministry of Labour Relations. In this distributive each consist of processes with the respective positions that compose and hierarchical levels are determined in leadership positions considered free appointment and removal, likewise, have given different levels and degrees of career servers defined as public servants support (considered non-professional ) and public servants in general (considered as professionals), that taking into account the level of responsibility in each of the processes listed above and whose functions and activities are related to: Address Technical Area, Coordination Process, Process Monitoring, Process Implementation and Enforcement of Administrative and Technical Processes. To complete the process of institutional organization, we propose a suitable model of organizational structure and administrative and management processes, the same that will enable the National University of Loja, assess the efficiency and effectiveness of the functions and activities that develop each of university public servants. The whole proposal is legal and legitimate, since, were used as main bibliographical source different laws as: Public Service Law, Planning Law and Public Finance, Higher Education Law, and the University Statutes and Regulations. All this compendium of secondary research sources define Human Resource responsibilities of each of the administrative departments of the National University of Loja, all based on a profile of requirements for the development of administrative and management functions.